Effect of Ni addition and cryogenic hardening on the mechanical and tribological properties of self-lubricating steels produced by MIM. (26th May 2020) - Araya, N.; Vieira, L. E.; de Mello, José Daniel B.; Neves, G. O.; Binder, C.; Klein, A. N.; Aguilar, C.
ABSTRACT: This paper addresses the relation between mechanical properties and tribological behaviour of self-lubricating steels produced by in-situ dissociation of SiC. Literature shows that an increase in the mechanical strength of these materials lowers their friction coefficient and wear rates. These works have studied steels with mechanical strength up to 800 MPa, but it is unclear if this trend continues with further increments of mechanical strengths. To tackle this question, self-lubricating steels with Ni and Mo were sintered, half of the samples with 8 wt-% Ni were treated cryogenically hardened. Results show that this trend does not escalate with mechanical strength, furthermore, when ductility is low, graphite reservoirs are not easily accessed, and lubrication is incomplete. Also, plastic deformation allows to better distribute the load of the counter body at the surface, which reduces the wear rates of the specimens and the counter bodies.